2-Acetyl-3-(benzoylamino)-1-benzofuran - Iskeleli, NO; Kazak, C; Kirilmis, C; Koca, M (Int Union Crystallography, 2005)
The title compound, C17H13NO3, displays the characteristic features of benzofuran derivatives. The molecule is nearly planar. An intramolecular N-H center dot center dot center dot O hydrogen bond, together with pi - pi stacking interactions, helps to stabilize the structure.